Estado da arte do sequenciamento genômico na pecuária - Pereira, Guilherme Luis; Rosa, Kamila O.; Curi, Rogério Abdallah [UNESP]; Regitano, Luciana Correa de Almeida; Mota, Marcílio Dias S. da (My University, 2013)
There has been a lot of advance in genomics since 1975 when the possibility to determine the nucleotide sequence of a genome was described. In the 90’s the human genome sequencing was started and it was greatly favored by advances in computer technologies. In the last ten years the development of next generation sequencing technologies allowed the sequencing of millions of bases at low cost and in a shorter time compared to the previous technologies. After the conclusion of the human genome project, several initiatives to sequence the genome of domestic animal species were taken, resulting in a large amount of data that is redirecting the goals of genetic studies in domestic animals. The aim of this review was to describe the present situation of the sequencing initiatives on the main domestic animal species of economical interest as well as to list the most important tools available to access the genomic information.

Desde que a possibilidade de determinar a sequência nucleotídica de genomas surgiu em 1975, muitos foram os avanços da genômica. Na década de noventa teve início o sequenciamento do genoma humano, viabilizado em grande parte pelos avanços nos métodos computacionais. Nos últimos dez anos, o advento de tecnologias de sequenciamento de nova geração permitiu o sequenciamento de milhões de bases a baixo custo e em curto espaço de tempo quando comparadas às técnicas de sequenciamento anteriores. Após a conclusão do projeto genoma humano, muitas iniciativas foram tomadas para a realização do sequenciamento de diversas espécies domésticas, gerando grande volume de dados, e redirecionando os estudos genéticos. Esta revisão teve como objetivo descrever o estado atual do sequenciamento das principais espécies de animais domésticos de interesse econômico, bem como de expor as ferramentas mais utilizadas no acesso às informações genômicas.
Status of the art sequencing genome on livestock
Keywords: BAC; Genoma; Next Generation Sequencing; SNP; WGS